E-learning using Robust Information Technology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid evolution in information technology, software, and hardwareequipment has greatly affected emerging and improving new educationapproaches called E-learning. Universities and stakeholders have steppedforward and started investing in this learning type to increase highereducation revenue. On the other hand, students become greedy to join onlinelearning regardless of geographical area, students' ethnicity, and age. Thescholars showed that online learning outperformed face-to-face education toobtain knowledge and satisfy their needs. However, some challenges couldface online learning, such as the sense of isolation as students are virtuallyconnected and technology could be difficult for most students. This studyhighlights online literature, challenges, and, on top of that, givingrecommendations to enhance a quality of e-learning